2021
DOI: 10.1177/02646196211059756
|View full text |Cite
|
Sign up to set email alerts
|

“Like I’m flying”: Capoeira dance experiences of youth with visual impairments

Abstract: Participation in dance programs is associated with physical and psychosocial health among individuals with and without disabilities. However, literature centered on the dance participation experiences of youth with visual impairment remains scarce. Therefore, the purpose of this study was to explore the experiences of youth with visual impairments in a 3-week capoeira dance program. Fourteen adolescents with visual impairments (eight boys, six girls, aged 13–18 years old) were selected for participation in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In contrast, studies involving experienced capoeira players have shown that both men 7 and women 8 have reduced performance declines with age. Such results suggest that the pattern of reduction in capoeira players' performance with aging, associated with other benefits from the practice of capoeira [9][10][11] , may be related to health variables and the practitioners' QoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studies involving experienced capoeira players have shown that both men 7 and women 8 have reduced performance declines with age. Such results suggest that the pattern of reduction in capoeira players' performance with aging, associated with other benefits from the practice of capoeira [9][10][11] , may be related to health variables and the practitioners' QoL.…”
Section: Introductionmentioning
confidence: 99%
“…* p<0.001 for significant difference from normative values; # p<0.001 for significant difference from male combat sports/martial arts practitioners. Data are represented as mean±standard deviation.Rev Assoc Med Bras 2022;68(11):1530-1536…”
mentioning
confidence: 99%